Avaliação sorológica e molecular de pacientes com quadro clínico de dengue símile atendidos no hospital das forças armadas - Sousa, Adriano Roberto Vieira de (2019)
Arboviruses are a public health problem due to outbreaks and diseases caused in several countries around the world. They are transmitted to humans and other animals through the bite of mosquito vectors, mainly of the genus Aedes. Dengue, Zika, Chikungunya and Mayaro viruses are arboviruses that share similar clinical symptoms (dengue-like), commonly fever, rash, myalgia and arthralgia. The differential diagnosis is performed through serology and / or molecular biology techniques. In Brazil these arboviruses are endemic and have a wide geographic distribution. Due to its reemergence, several rapid diagnostic kits are available in the market, and studies are needed to prove the effectiveness of these tests. The present study aims to evaluate the efficacy of two rapid lateral flow immunochromatography diagnostic kits - Orange Life® and Bahiafarma® . Both kits are available in the market. During the period from February to April 2017, 421 samples of whole blood were collected from dengue-like patients at the Hospital das Armed Forces, Brasília-DF. The hospital performed a serological screening for the following antigens - Dengue NS1, Dengue Anti-IgM/IgG and Chikungunya IgM using the Orange Life® kit. After sorting, two groups were selected according to inclusion and exclusion criteria based on Serological Profiles. Group 1 was 58 non-reactive samples for Dengue NS1, Dengue Anti-IgM/IgG and Chikungunya IgM antigens. Group 2 was 24 reagent samples for Dengue NS1 antigen. The samples were sent to the Laboratory of Molecular Genetics and Cytogenetics of the Federal University of Goiás where they were screened using the kit recommended by the Ministry of Health-Bahiafarma® Zika Combo Anti-IgM/IgG virus. Polymerase Chain Reaction (Real-time and Conventional) techniques were used for the detection of viral RNA. The molecular results for Group 1 were 4 positive samples for Dengue, 5 for Zika, 17 for Chikungunya and 2 for Mayaro. Two positive samples for Mayaro were sequenced, observing homology with other available sequences. For Group 2, 6 samples were positive for Dengue, 5 for Zika and 3 Chikungunya. Comparing the molecular results, the serological kit of Bahiafarma® Zika Combo Anti-IgM/IgG virus presented 100% specificity with a negative predictive value of 87.8%. Orange Life® serological kits showed - Dengue NS1 42.8% and 61.5% sensitivity and specificity; Dengue IgM 93% specificity with 83.56% negative predictive value; Chikungunya IgM 72.2% specificity with 56.4% negative predictive value. The results obtained in this work demonstrate that the tests evaluated have lower sensitivity and specificity than the recommended ones when the molecular results are compared. Health professionals are advised to choose the most appropriate test according to detection windows by watching the onset days of symptoms.